Identification of Potential Genes in Pathogenesis and Diagnostic Value Analysis of Partial Androgen Insensitivity Syndrome Using Bioinformatics Analysis - Peng, Yajie; Zhu, Hui; Han, Bing; Xu, Yue; Liu, Xuemeng; Song, Huaidong; Qiao, Jie (Frontiers in Endocrinology, 2021)
Abstract Background: Androgen insensitivity syndrome (AIS) is a rare X-linked genetic disease and one of the causes of 46,XY disorder of sexual development. The unstraightforward diagnosis of AIS and the gender assignment dilemma still make a plague for this disorder due to the overlapping clinical phenotypes. Methods: Peripheral blood mononuclear cells (PBMCs) of partial AIS patients and healthy controls were separated, and RNA-seq was performed to investigate transcriptome variance. Then, tissue-specific gene expression, functional enrichment, and protein–protein interaction (PPI) network analyses were performed, and the key modules were identified. Finally, the RNA expression of differentially expressed genes of interest was validated by quantitative real time polymerase chain reaction (qRT-PCR). Results: In our dataset, a total of 725 differentially expressed genes (DEGs) were captured, with functionally enriched reproduction and immune-related pathways and GO functions. The most highly specific systems centered on hematologic/immune and reproductive/endocrine systems. We finally filtered out CCR1, PPBP, PF4, CLU, KMT2D, GP6 and SPARC by the key gene clusters of the PPI network and manual screening of tissue-specific gene expression. These genes provide novel insight into the pathogenesis of AIS in the immune system or metabolism and bring forward possible molecular markers for clinical screening. The qRT–PCR results showed a consistent trend in the expression levels of related genes between PAIS patients and healthy controls. Conclusion: The present study sheds light on the molecular mechanisms underlying the pathogenesis and progression of AIS, providing potential targets for diagnosis and future investigation.